Legal Implications of the Application of Electronic Certificates on Legal Certainty and Land Dispute Resolution - Rini, Indrati; Bachtiar, Sony (Publikasi Indonesia, 2025)
With an Electronic Certificate confirming the legal status of land, disputes regarding ownership and land boundaries can be minimized. This certificate is a valid means of proof and can be accounted for in court, making it easier to resolve land disputes. Legal certainty of the subject and object of the land plot in the electronic certificate must be integrated with the Warkah Document. The validity of land object data does not only depend on electronic certificates, but also on supporting documents or documents. Electronic systems make it easier to store and access these documents, thereby minimizing the risk of loss or damage to records.